The impact of the financial characteristics of companies on the capital budget an analytical study of the industrial and agricultural sectors in Iraq (NTU journal for Administrative and Human Sciences (JAHS), 2022)
The aim of the research is to measure and analyze the impact of the financial characteristics of companies represented by the prevailing patterns for each of (Current assets, Equity, Profits growth, Short liabilities, and current activities revenues) on the Capital budget of a sample of companies from both the industrial and agricultural sectors listed in the Iraq Stock Exchange for the period from (2010-2020), based on the research problem that was formulated by the following question: What are the most important financial characteristics that affect making and making investment decision for the research sample companies? From which emerged the research hypothesis, which states that Capital budget decisions of all kinds are affected by many indicators within its financial environment and vary in direction and strength and according to the type of variable, through the analysis of panel data for explanatory variables based on the Eviews 10 statistical program. And inverse to all explanatory variables in the Capital budget for both sectors with the exception of profit growth in the industrial sector, which appeared with an insignificant effect, and the research reached a set of recommendations perhaps the most important of which is that industrial companies withhold part or their profits for the purpose of directing them towards capital investment and relying on internal financing for the two sectors during the research period.